2019
DOI: 10.7759/cureus.6320
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Patient and Student Experience at a Longstanding Student-run Free Clinic in Cape Town, South Africa

Abstract: Background Student-run free clinics (SRFCs) combine medical student learning with the provision of free health care. A comprehensive evaluation of patient experience at SRFCs is needed to ensure a balance between valuable clinical experience for students and enhancement of patient care. The aim of this study was to describe patient and medical student perception of care at a longstanding SRFC at the University of Cape Town (UCT). Methods We conducted an observational study at the Students' Health and Welfare C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Thirteen were controlled-group studies [ 20 , 21 , 36 , 37 , 46 , 47 , 49 , 50 , 60 , 61 , 59 , 70 , 72 ], among which two were randomized [ 46 , 60 ]. Five main types of educational interventions were evaluated: global curriculum dedicated to social accountability [ 20 , 21 , 36 , 46 , 47 , 48 , 50 , 51 , 53 , 60 , 61 , 72 , 77 ]; experiential community-based learning [ 37 , 41 , 70 ]; volunteering in student-run free clinics [ 55 , 58 , 69 , 76 ], traditional didactic learning ,, [ 31 , 39 , 65 ] and online curriculum [ 75 ]. Experiential community-based learning and global curricula showed the greatest positive impact on MS-ATU, whereas volunteering in student-run free clinics and traditional learning showed inconsistent results.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen were controlled-group studies [ 20 , 21 , 36 , 37 , 46 , 47 , 49 , 50 , 60 , 61 , 59 , 70 , 72 ], among which two were randomized [ 46 , 60 ]. Five main types of educational interventions were evaluated: global curriculum dedicated to social accountability [ 20 , 21 , 36 , 46 , 47 , 48 , 50 , 51 , 53 , 60 , 61 , 72 , 77 ]; experiential community-based learning [ 37 , 41 , 70 ]; volunteering in student-run free clinics [ 55 , 58 , 69 , 76 ], traditional didactic learning ,, [ 31 , 39 , 65 ] and online curriculum [ 75 ]. Experiential community-based learning and global curricula showed the greatest positive impact on MS-ATU, whereas volunteering in student-run free clinics and traditional learning showed inconsistent results.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, there was inconsistency across disciplines and institutions around in the use of labels, such as: student-assisted, -led, -run, or -facilitated. Additional terms identified in a separate, systematic review of international student-led clinics (submitted) included service-learning (examples [42][43][44][45] ) and student free-clinics (examples [46][47][48][49][50][51][52] ), the apparent distinction for these being the model of operation making no charge on service users, whereas as some, but not all, student clinics charge nominal fees to cover costs. Across all variations, the initiatives described appeared to fulfil the same purpose -addressing a community health need and generating authentic learning experiences for the student.…”
Section: Discussionmentioning
confidence: 99%
“…Heller et al [24] 2019 Survey, 52 medical students Surveys before and after volunteering at the SRC showed that 13/52 students had an increased desire to pursue primary care.…”
Section: Retrospective Study 908 Medical Studentsmentioning
confidence: 99%
“…Ultimately, seven studies (two retrospective studies and five prospective surveys) were included in this review, all of which are indexed by the outcome group in Tables 2 - 4 [ 21 - 27 ]. The studies conducted by Tran et al, Vaikunth et al, and Heller et al each met the inclusion criteria of two outcome groups and are included twice each in Tables 2 - 4 [ 21 , 23 , 24 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation